O processo de construção técnica e política para a instituição da Outorga Onerosa do Direito de Construir no novo Plano Diretor de Belo Horizonte - Rosiele Fraga Nogueira da Matta (2023)
This research aims to carry out a critical analysis of the technical and political construction process for the institution of the sale of building rights, in Belo Horizonte. This study is part of the recent context of the debate on the Bill of the city's new Master Plan, which was processed at the Municipality of Belo Horizonte from 2015 to 2019 and was approved in August 2019 as Law 11,181, of 2019. This law institutes the new Master Plan of the Municipality and the aforementioned management instrument for the valorization of urban land, supported by the single and unitary basic utilization coefficient for the entire municipal territory. From the entry of the new Master Plan Bill in the City Council in 2015, until its approval in 2019, the main point of conflict was the legitimacy of implementing the sale of building rights in Belo Horizonte, as the equalization of rights, the redistribution of more land value and the fair distribution of the burdens and benefits of urbanization, aspects that seemed to be obvious benefits in the eyes of the instrument's defenders, gained, however, different interpretations among the agents that make up the urban dispute scenario. By unveiling the process of instituting the sale of building rights in Belo Horizonte, the investigation not only broadens the understanding of the instrument, but mainly, it unveils, based on Bourdieu's field, agent and habitus concepts, the conflicts between the various agents in the production of urban space manifested in this discussion. Therefore, the research strips away the aspects of the tool that were contested by some groups in society and highlights the most varied interests that lie behind the strategies adopted by these different agents in the production of urban space. For this purpose, qualitative methods are used, with documentary research techniques, through the analysis of reports from the time, consulting the social media pages of the movements that discussed the theme, examining the dissemination materials that were broadcast, as well as the evaluation of the minutes of hearings and public events on the new Master Plan.